Autism spectrum disorders: head circumference and body length at birth are both relative. (28th June 2013) - Grandgeorge, Marine; Lemonnier, Eric; Jallot, Nelle
Abstract: Aim: Although the body length and weight of an infant are related to head circumference, little research on ASDs has examined these factors. Our study compared the head circumferences of neonates who were later diagnosed with ASD with a control group. Additional comparisons on morphological disproportions at birth included the head circumference‐to‐height and head circumference‐to‐weight ratios. Methods: We recruited 422 children with ASD and 153 typically developing children. Head circumference, body length and weight at birth were collected and standardized as percentile scores according to gestational age and gender. Results: Our results revealed that genuine macrocephaly was significantly higher in children with other pervasive developmental disorders compared with the control group. This difference was not observed with regard to genuine microcephaly. Relative macrocephaly and relative microcephaly were significantly more frequent in children with autism disorder compared with the control group with regard to body length. Conclusions: The differences in relative macrocephaly and microcephaly, as well as in other parameters, between diagnostic subgroups suggest that the presence of several neurological mechanisms plays a role in the later expression of different phenotypes. An increased head circumference‐to‐body length ratio in newborns may be a factor to follow that could be related to ASD. Abstract :